How Does Myofascial Physical Therapy Attenuate Pain in Chronic Pelvic Pain Syndrome?. (12th December 2019) - Grinberg, Keren; Weissman-Fogel, Irit; Lowenstein, Lior; Abramov, Liora; Granot, Michal
Abstract : Background . Chronic pelvic pain syndrome (CPPS) is a multifactorial disorder comprising structural and functional muscular abnormalities, a dysfunctional pain system, and psychological distress. Myofascial physical Therapy (MPT) that is targeted at improving pelvic muscle functioning is considered a first line nonpharmacological treatment for CPPS, although the precise mechanisms that lead to symptoms alleviation have not yet been elucidated. Purpose . This longitudinal study aimed to examine the local and systemic effects of MPT intervention, including biopsychophysiological processes, among CPPS patients. Methods . The study included 50 CPPS women. Morphologic assessment of the levator ani and quantitative sensory testing of the pain system were applied alongside with evaluation of pain-related psychological factors using designated questionnaires. All measures were evaluated both before and after MPT in 39 patients. The long-term effects of MPT were evaluated by clinical pain reports obtained at 3 and 9 months following MPT that were compared with a nontreated group of 11 untreated CPPS women. Results . Along with an improvement in the clinical pain intensity (p = 0.001 ) and sensitivity to experimental pain tests (p = 0.001 ) following MPT, the results also indicate that MPT has anatomical, psychological, and social therapeutic effects (p = 0.04 ; p = 0.001 ; p = 0.01, respectively). Furthermore, clinical pain evaluation at 3 and 9 months after MPT revealed a significant improvement in women who received treatment (p = 0.001 ). Conclusions . The findings of this pilot study suggest multisystemic (direct and indirect anatomical, neurophysiological, and psychological) effects of MPT on the multifactorial pain disorder of CPPS and therefore place MPT as a mechanism-based intervention.